Control of the belt speed at unbalanced loading of the conveyor - Pihnastyi, O. M. (Національний технічний університет "Дніпровська політехніка", 2019)
Purpose. Development of algorithms for controlling the speed of the conveyor belt, based on the distributed model of the transport system, containing partial differential equations Methodology. To calculate the parameters of a conveyor line with a variable speed of material motion, an instrument of mathematical physics is used. Findings. Comparative analysis of conveyor transport system models is performed. Application of partial differential equations for simulating transport systems of conveyor type, which are complex dynamic distributed systems, is substantiated. A non-dimensional model of a conveyor system in instantaneous approximation with the use of partial-derivative equations is presented. A system of characteristic equations is recorded and a solution is developed which defines the value of material flow and material density at an arbitrary point of time for the given point of the transportation route. An expression is obtained which defines the value of material delay in the transport system depending on the velocity defect law for conveyor belt movement. Transition period time is determined during which the output material flow is defined by linear density of material disposition along the transportation route. Dependences for the material linear density and material flow for the steady state condition are defined. The performance criterion of control of flow parameters of the conveyor system is recorded and a solution of the problem of optimal control of conveyor belt speed providing the relay control mode with the minimum power consumption for material movement is found. An example of control algorithm development is given. Originality. PDE-models of transport systems of conveyor type and energy-saving algorithms for controlling such systems have been improved. Practical value. The proposed method for calculating the parameters of the conveyor line, which is a dynamic distributed system, can be used to design systems for optimal control of flow parameters of transport systems of conveyor type.

Мета. Розробка алгоритмів керування швидкістю руху конвеєрної стрічки, заснованих на розподіленій моделі транспортної системи, що містить рівняння у приватних похідних. Методика. Для розрахунку параметрів конвеєрної лінії зі змінною швидкістю руху матеріалу використано апарат математичної фізики. Результати. Проведено порівняльний аналіз моделей конвеєрних транспортних систем. Обґрунтовано використання рівнянь у приватних похідних для моделювання транспортних систем конвеєрного типу, що є складними динамічними розподіленими системами. Представлена безрозмірна модель конвеєрної системи в одномоментному наближенні з використанням рівнянь у приватних похідних. Записана система характеристичних рівнянь і побудоване рішення, що визначає величину потоку матеріалу та щільність матеріалу в довільний момент часу для заданої точки маршруту транспортування. Отримано вираз, що визначає величину затримки матеріалу у транспортній системі в залежності від закону зміни швидкості руху конвеєрної стрічки. Визначено час перехідного періоду, протягом якого вихідний потік матеріалу визначається лінійною щільністю розміщення матеріалу вздовж транспортного маршруту. Визначені залежності для лінійної щільності матеріалу й потоку матеріалу для сталого режиму. Записано критерій якості управління потоковими параметрами конвеєрної системи та отримане рішення задачі оптимального управління швидкістю конвеєрної стрічки, що забезпечує релейний режим управління за мінімальних питомих витрат електроенергії на переміщення матеріалу. Наведено приклад побудови алгоритму управління. Наукова новизна. Полягає в удосконаленні PDE- моделей транспортних систем конвеєрного типу та енергозберігаючих алгоритмів управління такими системами. Практична значимість. Полягає в тому, що запропонований спосіб розрахунку параметрів конвеєрної лінії, який є динамічною розподіленою системою, може бути використаний для проектування систем оптимального управління потоковими параметрами транспортних систем конвеєрного типу.
Управління швидкістю руху стрічки при нерівномірному завантаженні конвеєра
Keywords: conveyor; PDE-model of production; distributed system; PDE-model production lines; PDE-model; production line; belt speed; work in progress; конвеєр; розподілена система; PDE-модель; потокова лінія; швидкість стрічки